Heterojunction photocatalyst as well as preparation method and application thereof
By using the low-temperature epitaxial growth technology of CuS@VS4 heterojunction photocatalytic material, the problems of uncontrollable lattice defects and morphology of VS4 material in the field of photocatalysis have been solved, achieving targeted repair of sulfur defects and significant improvement of photocatalytic performance, which is suitable for the treatment of antibiotic pollution in water bodies.
Patent Information
- Application Number
- CN202511154312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-11-28
AI Technical Summary
In the existing technology, the application of vanadium tetrasulfide (VS4) materials in the field of photocatalysis is limited by the problems of lattice defects and uncontrollable morphology. Moreover, traditional repair methods are not green or simple enough, and new defects are easily introduced during the heterojunction recombination process.
A heterojunction was formed by combining CuS and VS4, and CuS nanosheets were epitaxially grown on the VS4 surface using a low-temperature epitaxial growth technique. By utilizing the strong bond energy difference and slow nucleation kinetics of the Cu2+- sulfur source precursor, targeted repair of sulfur defects was achieved, avoiding the introduction of new defects during the recombination process.
It significantly improved the photocatalytic degradation performance, increasing the photocurrent by 200 times, achieving a tetracycline hydrochloride degradation rate of 97.9%, with almost no degradation after 5 cycles. Rhodamine B and hexavalent chromium ions also showed significant degradation effects, solving the bottleneck in the application of VS4 materials in the field of photocatalysis.
Smart Images

Figure CN121016790A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic materials technology, specifically to a heterojunction photocatalyst, its preparation method, and its application. Background Technology
[0002] Antibiotic pollution in water bodies has become a global environmental crisis, and traditional biological / physicochemical treatment technologies are insufficient for removing low concentrations of antibiotics. While photocatalysis can utilize solar energy to degrade pollutants, it faces bottlenecks such as high carrier recombination rates and difficulties in catalyst recovery. Vanadium tetrasulfide (VS4) is considered an ideal candidate material due to its narrow bandgap and near-infrared response, but its practical application is limited by inherent defects (lattice defects) in the VS4 material and defects in the synthesis process. Currently, the mainstream method is the high-temperature solvothermal method. For example, patent document CN114744152B discloses a vanadium tetrasulfide / vanadium carbide composite material, its preparation method, and its applications. Although the prepared VS4 material exhibits good photoelectric properties, its inherent lattice defects and uncontrollable morphology make further performance improvements difficult, significantly limiting the application of VS4 in the field of photocatalysis. To overcome these drawbacks in the application of VS4 in photocatalysis, solving the problems of lattice defects and uncontrollable morphology is essential.
[0003] Regarding lattice defects, current methods for controlling lattice defects (such as defect repair) mainly employ the following: ① High-temperature sulfidation method (such as H2S annealing): The literature "Annealing for intrinsic point-defect control and enhanced solar cell performance: the case of H2S and tin sulfide (SnS)" (MDF, Department of Materials Science and Engineering, MIT, 2015) reports on H2S / High-temperature annealing with H2 mixed gas can regulate the carrier concentration of SnS thin films and improve the photovoltaic efficiency of SnS-based solar cells by 98.4% by repairing sulfur defects. However, it cannot be applied to powder catalysts, and H2S is highly toxic, which does not conform to the trend of green synthesis. ② Anion doping (such as N doping): The patent document with publication number CN118448609A discloses a method for preparing high-capacity porous heterojunction tin-based sulfide for sodium batteries. Although N-doped SnO / tin sulfide heterojunction porous sheet material is prepared, the doped ions are prone to destroying the periodicity of the crystal, resulting in new lattice distortion. ③ Laser annealing: The literature "Athermal repair of nanoscale defects in optical materials using a femtosecond laser" (Nanoscale, 2017, 9(44): 17233-17240.) reports the use of femtosecond laser to irradiate fused silica to repair defects and interstitial atoms generated by ion implantation, which significantly improves the carrier dynamics. However, this method has high requirements for instruments and equipment and is not suitable for large-scale repair production. In summary, existing technologies lack green, simple, and gentle repair methods.
[0004] In terms of morphology control, ball milling, as a common material preparation technique, has advantages over high-temperature solvothermal methods. However, the huge local energy generated by high-speed collisions, compression, and shearing between materials during ball milling can induce lattice defects (sulfur defects). Therefore, considering the adverse effects of ball milling on sulfur defects, this preparation method is obviously unsuitable for VS4. Consequently, when VS4 is used to construct heterojunction composites with other materials, lattice defects will be further aggravated during the heterojunction composite process.
[0005] Recent studies have focused on improving the charge separation efficiency of V-based sulfide materials through heterojunctions to expand the application range of VS4 in the field of photocatalysis. For example, the literature "A Z-Scheme strategy utilizing ZnIn2S4 and hierarchical VS2 microflowers with improved charge carrier dynamics for superior photoelectrochemical water oxidation" (Chemistry-An Asian Journal, 2019, 14(24): 4607-4615.) reported that under the action of the built-in electric field of the heterojunction, the charge carrier lifetime inside the composite material was increased from 2.45 ns to 1.31 ns. However, this study still neglected the influence of interfacial chemical defects of V-based sulfide materials in the heterojunction composite process.
[0006] Therefore, how to obtain a heterojunction photocatalytic material based on V-based sulfide materials that can repair sulfur defects and does not induce new defects during the heterojunction recombination process is a technical challenge that urgently needs to be solved by researchers in this field.
[0007] Therefore, this patent application is filed. Summary of the Invention
[0008] To address the above problems, this invention provides a heterojunction photocatalyst, along with its preparation method and applications. The CuS@VS4 heterojunction photocatalytic material obtained by this invention not only effectively repairs sulfur defects (chemical defects) in VS4 but also avoids the exacerbation of sulfur defects during the heterojunction composite process. The CuS@VS4 heterojunction composite material of this invention achieves synergistic effects of sulfur defect repair and heterojunction, significantly improving photocatalytic degradation performance and providing an efficient solution for the treatment of antibiotic pollution in water bodies.
[0009] The first objective of this invention is to provide a method for preparing a heterojunction photocatalyst, which uses CuS and VS4 to form a heterojunction. The process of forming the heterojunction is as follows: CuS nanosheets are epitaxially grown on VS4 material to obtain CuS@VS4 heterojunction photocatalytic material.
[0010] This invention selects CuS and VS4 to construct a heterojunction. This is because research has shown that V has a greater metallicity than Cu, therefore the bond energy of the VS bond (approximately 456 kJ / mol) is greater than that of the Cu-S bond (approximately 289 kJ / mol). Thus, in the presence of VS4 and S... 2- With Cu 2+ In a system where the bond energy difference is large, S 2-Preferential formation of chemical bonds with high bond energy, namely VS bonds, while S bonds... 2- When it combines with V, it occupies the position of sulfur vacancies, thereby achieving the effect of repairing sulfur defects.
[0011] Furthermore, during the heterojunction recombination process, due to Cu 2+ The Ksp of the formed sulfides (such as CuS) is approximately 6.3 × 10⁻⁶. -36 Although small, Cu 2+ With S 2- The reaction activation energy of Cu is relatively high, and Cu 2+ It readily forms weak coordination with defect sites on the VS4 surface (lowering the diffusion barrier), making S 2- It is easier for it to diffuse to the defect site first and combine with V (repairing the defect), rather than rapidly nucleating to form CuS. This results in a two-parameter coupling of "bond energy difference + gradual nucleation" in the CuS@VS4 system, achieving the purpose of modifying sulfur defects without exacerbating them during the recombination process. This solves the current technical difficulties in preparing heterojunction photocatalytic materials based on VS4.
[0012] Meanwhile, the present invention employs epitaxial growth technology to form tight chemical bonds, which can also induce more significant and large-scale charge transfer, which is beneficial to sulfur defect repair. This can also be demonstrated from the results of the spin electron resonance (ESR) spectrum of Comparative Example 6.
[0013] As a preferred design, the epitaxial growth process employs low-temperature oil bath conditions; During the low-temperature oil bath, the oil bath temperature is 80~100℃. o C, the reaction time is 1~3 hours. Preferably, the oil bath temperature is 80℃.
[0014] In this invention, a low temperature (80~100℃) is used during the epitaxial growth process. o C) Oil bath conditions are necessary because, in the process of eliminating sulfur defects, in addition to bond energy (thermodynamic factors), there are also multiple factors such as reaction kinetics (e.g., nucleation rate, diffusion capacity), solubility of metal sulfides (solubility product), and hydrolysis / coordination behavior of metal ions. These factors significantly affect the reaction pathway.
[0015] In reaction kinetics, under low-temperature oil bath conditions, the reaction relies more on "rapid nucleation" than on thermodynamic equilibrium. If metal ions react with S... 2- If the reaction activation energy is low and the nucleation rate is fast (e.g., the critical size for crystal nucleation is small), then the reaction will preferentially generate its own sulfides rather than diffuse to the VS4 surface to replenish defects (the reaction at the defect sites requires S). 2- Overcoming the diffusion barrier is kinetically slower.
[0016] Regarding the solubility of metal sulfides, if the metal ions react with S... 2-The resulting sulfides have extremely low solubility (Ksp is very small, even though their metal-S bond energy is less than the VS bond energy, S 2- It will also preferentially combine with metal ions to form precipitates (because precipitation is a thermodynamically spontaneous process and kinetically rapid nucleation), rather than diffuse to the sulfur defects of VS4 and combine with V.
[0017] In the hydrolysis / coordination behavior of metal ions, if the metal ion is easily hydrolyzed in aqueous solution (e.g., forming hydroxides) or forms stable coordination compounds with solvents / additives, its affinity for S will decrease. 2- Its effective binding ability even indirectly promotes the independent nucleation of its own sulfides, rather than participating in the defect repair of VS4.
[0018] For the reasons mentioned above, not all of S 2- Metal ions with bond energies less than the V / S bond energy will behave like Cu. 2+ In this way, it preferentially combines with V in VS4 to eliminate sulfur defects. For example, the metal-S bond energies of the following metal ions are all lower than the VS bond energy, but under low-temperature oil bath conditions (taking 80℃ as an example), they will preferentially form their own sulfides rather than replenish the sulfur defects in VS4: (1) Zn 2+ Bond energy comparison: The Zn-S bond energy is approximately 380~420 kJ / mol (less than the VS bond energy, with a bond energy difference of ΔE = 50 kJ / mol). Actual reaction path: In an 80℃ oil bath, Zn... 2+ S produced by the decomposition of thioacetamide (TAA) 2- ZnS will preferentially form (as shown in Comparative Example 2 in the specific implementation, Table 1 and...). Figure 1 All of these prove this point), rather than supplementing the sulfur defect of VS4. This is because the solubility of ZnS is extremely low (Ksp≈1.6×10). -24 ), as long as there are trace amounts of S in the solution 2- Zn 2+ It will quickly connect with S 2- Combined to form precipitate (nucleation rate is extremely fast); at low temperatures, the nucleation activation energy of ZnS is much lower than that of S. 2- The activation energy for diffusion to VS4 defect sites and binding to V is more readily available kinetically; Zn 2+ It is not easily hydrolyzed under neutral to weakly acidic conditions, and can maintain a high concentration of free state, further accelerating the formation of ZnS.
[0019] (2) Pb 2+ Bond energy comparison: The Pb-S bond energy is approximately 350~390 kJ / mol (less than the VS bond energy, with a bond energy difference of ΔE = 106 kJ / mol). Actual reaction pathway: Pb 2+ With S 2-At low temperatures, PbS is preferentially formed rather than used to repair sulfur defects in VS4. This is because the Ksp of PbS is approximately 9.0 × 10⁻⁶. -29 The solubility is much lower than the "adsorption-binding" equilibrium concentration of sulfur defects in VS4, S 2- It will prioritize Pb 2+ Combined to form a precipitate; at low temperatures, Pb 2+ With S 2- The reaction activation energy is low (no need to overcome the diffusion barrier on the VS4 surface), and the nucleation rate is much faster than that of S. 2- The diffusion rate to defect sites leads to the independent formation of PbS (as shown in Table 1 and Table 2 for the sample in Comparative Example 3 in the specific implementation). Figure 1 All of these prove this point.
[0020] (3) Mn 2+ and In 3+ Mn and In are also less metallic than V, therefore the bond energies of Mn-S and In-S bonds are also less than those of V, thus S 2- It tends to combine with V to repair sulfur defects. However, the inventors discovered that the epitaxial growth of MnIn2S4 only repairs lattice distortions (structural defects) in VS4 materials, but cannot repair lattice sulfur defects (chemical defects). This is because although MnIn2S4 and VS4 are lattice-matched, and low-temperature epitaxial growth can release VS4 lattice stress to repair lattice distortions, MnIn2S4 is an extremely difficult-to-dissolve sulfide. 2- In solution, the nucleation and growth equilibrium of MnIn2S4 will be preferentially satisfied; Mn 2+ and In 3+ It exhibits high stability in solution (not easily hydrolyzed) and is compatible with S. 2- The reaction does not require overcoming complex coordination barriers and can rapidly generate MnIn2S4 nanosheets at low temperatures, kinetically suppressing the repair of sulfur defects in VS4 (as shown in Comparative Example 4 in the specific implementation, Table 1 and...). Figure 1 All of these results confirm this, showing that the MnIn2S4@VS4 sample still has a large number of sulfur defects.
[0021] Therefore, the above three types of metal ions do not follow the "preferential binding with V" rule. The core reason is: ZnS: insufficient bond energy difference (ΔE=50 kJ / mol) + ultra-low Ksp (10 -24 This represents the type with "weak thermodynamic driving but preferential kinetics"; PbS: significant bond energy difference (ΔE=106 kJ / mol) but Ksp is too low (10 -29 The first part represents the "thermodynamically feasible but kinetically suppressed" type; MnIn2S4: although the bond energy difference is unknown, the repair mechanism is different (repairing lattice distortion). When metal ions react with S... 2-The resulting sulfides have extremely low solubility (very small Ksp) and a much faster nucleation rate than S at low temperatures. 2- When the diffusion rate to VS4 defect sites is low, the reaction will preferentially generate its own sulfide even if the metal-S bond energy is lower than the VS bond energy.
[0022] In summary, this invention selects CuS and VS4 composite and performs heterojunction composite under low-temperature oil bath conditions. This prioritizes the repair of sulfur defects in VS4, rather than exacerbating the formation of sulfur defects during the composite process. The CuS@VS4 system is irreplaceable.
[0023] As a preferred design, it includes the following steps: Vanadium powder, thiourea and thioacetamide were mixed to obtain a slurry. The slurry was then ball-milled and post-processed to obtain VS4 powder. The obtained VS4 powder was added to glycerol, and then copper chloride and thioacetamide were added and ultrasonically dispersed. The mixture was then reacted in an oil bath and post-treated to obtain CuS@VS4 heterojunction photocatalytic material.
[0024] In this invention, VS4 powder is first prepared to obtain VS4 nanosheets with a size of 50-500 nm and a thickness of 10-100 nm. The nanosheets form a micron-flower-like structure with a flower size of 100-2000 nm. Next, CuS nanosheets are grown on the flower-like VS4 using an epitaxial growth method. The CuS nanosheets are formed during the ultrasonic dispersion of copper chloride and thioacetamide. When CuS nanosheets are grown in situ on the flower-like VS4, they exhibit a flower-like morphology. The final photocatalyst has nanosheets with a size of 100-1000 nm, a thickness of 10-80 nm, and formed micron-flowers with a size of 150-2500 nm.
[0025] This invention employs ball milling to prepare VS4 powder, which allows for better control of VS4 morphology. Compared to VS4 prepared by the high-temperature hydrothermal method, the specific surface area of VS4 prepared by ball milling is nearly doubled. While ensuring that VS4 possesses excellent specific surface area, CuS is used for sulfur defect repair. This fully utilizes the technical advantages of ball milling while addressing the problem of exacerbated sulfur defects caused by ball milling in VS4 preparation, thus resolving multiple technical challenges in applying VS4 to photocatalytic materials.
[0026] As a preferred design, when preparing VS4 powder, the molar ratio of sulfur source to vanadium powder is 1:(0.15~0.25), wherein the sulfur source is thiourea and thioacetamide; Vanadium powder, thiourea, and thioacetamide were added to ethanol and mixed. After ultrasonic dispersion, a mixed slurry was obtained. The volume ratio of the solid substances in the mixed slurry to the volume of ethanol was (1 mol): (0.25~2 L). The solid substances were thiourea, thioacetamide, and vanadium powder.
[0027] As a preferred design, when preparing VS4 powder, the ball milling speed is 200-300 rpm and the time is 5-18 h. Preferably, the grinding balls are made of zirconium oxide and have a size of 3 mm and 5 mm mixed.
[0028] In this invention, the preferred ball milling speed is as follows: if the speed is too low, the energy required for the reaction cannot be provided, and the VS material cannot be formed in the end (as in Comparative Example 11). If the speed is too high, the sulfur defects in the VS will be excessive, exceeding the targeted repair capacity of CuS, and thus the repair rate will decrease significantly (as in Comparative Example 10).
[0029] As a preferred design, during ball milling, the volume ratio of grinding balls to precursor raw materials is 1:(0.025~0.25), and the volume ratio of the total solid volume formed by the grinding balls and precursor raw materials to the volume of ethanol used in the ball milling reaction is 1:(1~5); wherein, the precursor raw materials include vanadium powder, thiourea and thioacetamide; And / or, during ball milling, the mode is set to rotate clockwise for 5-10 minutes, then pause for 1-2 minutes, then rotate counterclockwise for 5-10 minutes, and so on until the predetermined ball milling time is reached.
[0030] As a preferred design, the molar ratio of the VS4 material to copper chloride is 1:(1~5), and the molar ratio of the copper chloride to thioacetamide is 1:(1~1.5).
[0031] In this invention, the molar ratio of VS4 material to copper chloride is designed to be 1:(1~5), which ensures both the formation of CuS and the repair of sulfur defects. The molar ratio of copper chloride to thioacetamide is 1:(1~1.5) because thioacetamide, as a sulfur source, has two functions: firstly, to repair sulfur defects in VS4, and secondly, to react with copper chloride to generate CuS, with Cu:S=1:1. Therefore, a slightly higher amount of sulfur source is needed to satisfy these two functions.
[0032] As a preferred design, the post-processing for preparing VS4 powder involves sequentially filtering, washing, and drying. The post-treatment process after the oil bath reaction consists of centrifugation, washing, and drying in sequence. The centrifugation is performed in a centrifuge with a speed of 4000~8000 rpm for 2~10 minutes; The washing process involves washing the sample five or more times with deionized water and anhydrous ethanol alternately. The drying temperature is 70~90°C. o C, drying time is 6~24h.
[0033] A second objective of this invention is to provide a heterojunction photocatalyst, obtained by the preparation method described in any of the preceding claims.
[0034] A third objective of this invention is to provide the application of the heterojunction photocatalyst described above in the photocatalytic degradation of organic pollutants; The organic pollutant is at least one of tetracycline hydrochloride, phenol, rhodamine B, and phenol.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. This invention utilizes CuS and VS4 to form a heterojunction composite. Under low-temperature epitaxial growth conditions, Cu... 2+ -The sulfur source precursor generates a thermodynamic driving force due to the strong bond energy difference (ΔE=167 kJ / mol) and the slow nuclear kinetics, driving S... 2- Preferential migration to VS4 sulfur defects (chemical defects) enables targeted repair (according to data in Table 1, the ESR sulfur vacancy concentration significantly decreased from 9.25% to 0.75%). This mechanism requires the simultaneous fulfillment of the following conditions: (1) Thermodynamic conditions: Metal-S bond energy difference > 30% (threshold evidence: the repair rate is < 6% when the bond energy difference ΔE between Zn-S and VS is 11% according to the data in Table 1). (2) Kinetic conditions: Ensure the migration time of sulfur ions (kinetic evidence: high temperature failure in Comparative Example 1), and propose a targeted repair mechanism for sulfur defects for the first time.
[0036] 2. This invention reveals the importance of appropriate temperature for lattice repair and nucleation competition: at low temperatures, CuS has a high nucleation energy barrier, and S... 2- Prioritize defect repair; however, at high temperatures, the nucleation energy barrier of CuS drops sharply, and S... 2- It is rapidly consumed in the CuS growth process. This discovery breaks through the limitations of traditional heterostructure construction that only focuses on morphology / lattice matching, and for the first time incorporates reaction kinetic path control into interface engineering design.
[0037] 3. This invention yields a sulfur-defect-repairable heterojunction photocatalytic material based on V-based sulfide materials, which does not induce new defects during heterojunction recombination. This photocatalytic material exhibits a 200-fold increase in photocurrent. The heterojunction formation of VS4 and CuS synergistically drives efficient carrier separation, achieving a 97.9% degradation rate of tetracycline hydrochloride (120 min) with almost no degradation after 5 cycles. It also shows significant degradation effects on rhodamine B, hexavalent chromium ions, and phenol, especially rhodamine B and hexavalent chromium ions, with a degradation efficiency of almost 100% within 60 minutes, demonstrating its excellent multifunctional photocatalytic performance. Attached Figure Description
[0038] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be considered as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort. In the drawings: Figure 1 The images show the spin electron resonance (ESR) spectra of the samples prepared in Example 1 and Comparative Examples 1-9 of this invention.
[0039] Figure 2 The images show the X-ray diffraction (XRD) patterns of the samples prepared in Examples 1, 1-5, and 7-9 of this invention, wherein (a) is the XRD pattern of the samples prepared in Comparative Examples 5 and 7-9; and (b) is the XRD pattern of the samples prepared in Examples 1 and 1-4.
[0040] Figure 3 These are scanning electron microscope (SEM) images of the samples prepared in Examples 1, 1-4, and 7 of the present invention, wherein (a), (b), (c), (d), (e), and (f) are SEM images of the samples prepared in Comparative Example 7, Example 1, and Comparative Examples 1-4, respectively.
[0041] Figure 4 The figures show the photocatalytic performance of the samples prepared in Example 1 and Comparative Examples 1-12 of this invention. (a) and (b) are the degradation rate and degradation rate constant curves of tetracycline hydrochloride prepared in Example 1 and Comparative Examples 1-12, respectively.
[0042] Figure 5 The following is a graph showing the photocatalytic performance of the sample prepared in Example 1 of the present invention. (a) is a graph showing the rate of photocatalytic degradation of several common organic pollutants and heavy metals by the sample prepared in Example 1; (b) is a bar graph showing the stability of the sample prepared in Example 1 against tetracycline hydrochloride degradation after 5 cycles. Each cycle was a continuous degradation experiment lasting 2 hours.
[0043] Figure 6 The figures are current density curves of the samples prepared in Example 1 and Comparative Examples 1 to 9 of the present invention, wherein (a) is the current density curve of the samples prepared in Comparative Examples 5 to 9; and (b) is the current density curve of the samples prepared in Example 1 and Comparative Examples 1 to 4. Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. The illustrative embodiments and descriptions of this invention are only used to explain this invention and are not intended to limit this invention.
[0045] Example 1: This embodiment provides a method for preparing CuS@VS4 heterojunction photocatalytic materials using a low-temperature oil bath method, including the following steps: S1. Mix 10 mmol vanadium powder, 30 mmol thiourea and 24 mmol thioacetamide evenly, add 60 mL ethanol and ultrasonically disperse for 10 minutes to form a uniform slurry; S2. The mixed slurry is loaded into a grinding jar, which also contains a mixture of zirconia grinding balls with sizes of 3mm and 5mm. Ball milling was performed with a total solid volume ratio of grinding balls to precursor raw materials and ethanol volume of 1:3, and the rotation speed was controlled at 300 rpm. A cycle of 8 minutes forward rotation, 1 minute pause, and 8 minutes reverse rotation was adopted, and ball milling was continued for 10 hours. S3. After ball milling, rinse the mixture alternately with water and ethanol, and filter through a 400-mesh sieve to separate the grinding balls, unreacted vanadium powder, and other powders. Centrifuge at 4000 rpm for 4 minutes, then wash alternately with water and ethanol 5 times or more, and dry in a drying oven at 80°C. o Dry at C for 10 hours to obtain VS4 powder; S4. Add 1 mmol of VS4 material to 60 mL of glycerol and sonicate for 10 minutes. Then add 4 mmol of copper chloride and 4 mmol of thioacetamide and sonicate for 10 minutes to obtain a solid-liquid mixture. S5. Transfer the solid-liquid mixture to a 150 mL two-necked flask, then place the flask in an oil bath and react at 80 °C with continuous stirring for 2 h. After the reaction is complete, allow it to cool naturally. S6. The cooled sample was centrifuged at 4000 rpm for 4 minutes, washed 5 times alternately with water and ethanol, and dried in a vacuum oven at 80°C for 10 hours to obtain the low-temperature oil bath CuS@VS4 heterojunction photocatalyst material. The product is denoted as low-temperature CuS@VS.
[0046] Comparative Example 1: This comparative example provides a method for preparing CuS@VS4 heterojunction photocatalyst material using a high-temperature oil bath method. The difference from Example 1 is that steps S1-S6 are retained, but the step S5, "reacting at 80°C and stirring continuously for 2 hours," is replaced with "reacting at 140°C and stirring continuously for 2 hours." All other steps and parameters remain unchanged. The product is denoted as high-temperature CuS@VS.
[0047] Comparative Example 2: This comparative example provides a method for preparing ZnS@VS4 heterojunction photocatalyst material using a low-temperature oil bath method. The difference from Example 1 is that steps S1-S6 are retained, except that in step S4, "adding 4 mmol of copper chloride and 4 mmol of thioacetamide" is replaced with "adding 4 mmol of zinc chloride and 4 mmol of thioacetamide." All other steps and parameters remain unchanged. The product is denoted as ZnS@VS.
[0048] Comparative Example 3: This comparative example provides a method for preparing PbS@VS4 heterojunction photocatalyst material using a low-temperature oil bath method. The difference from Example 1 is that steps S1-S6 are retained, except that in step S4, "adding 4 mmol of copper chloride and 4 mmol of thioacetamide" is replaced with "adding 4 mmol of lead nitrate and 4 mmol of thioacetamide." All other steps and parameters remain unchanged. The product is denoted as PbS@VS.
[0049] Comparative Example 4: This comparative example provides a method for preparing MnIn2S4@VS4 heterojunction photocatalyst material using a low-temperature oil bath method. The difference from Example 1 is that steps S1-S6 are retained, except that in step S4, "adding 4 mmol of copper chloride and 4 mmol of thioacetamide" is replaced with "adding 4 mmol of manganese chloride, 8 mmol of indium chloride, and 20 mmol of thioacetamide." All other steps and parameters remain unchanged. The product is denoted as MIS@VS.
[0050] Comparative Example 5: This comparative example provides a method for preparing VS4 photocatalytic material treated with TAA (thioacetamide) using a low-temperature oil bath method. The difference from Example 1 is that steps S1 to S6 are retained, and only "adding 4 mmol of copper chloride and 4 mmol of thioacetamide" in step S4 is replaced with "adding 4 mmol of thioacetamide". All other steps and parameters remain unchanged. The product is denoted as TAA+VS.
[0051] Comparative Example 6: This comparative example provides a method for preparing a physically mixed CuS+VS4 photocatalytic material using a low-temperature oil bath method. The difference from Example 1 is that steps S4-S6 are retained, but VS4 material is not added in step S4. All other steps and parameters remain unchanged. Then, the VS4 material prepared in steps S1-S3 and the CuS prepared in steps S4-S6 are physically mixed at a molar ratio of 1:2.6 mmol. The product is denoted as the low-temperature CuS+VS4 physically mixed material.
[0052] Comparative Example 7: This comparative example provides a method for preparing VS4 photocatalytic material by ball milling, which differs from Example 1 in that steps S4-S6 are omitted, and only steps S1-S3 are retained. The product is denoted as VS.
[0053] Comparative Example 8: This comparative example provides a method for preparing CuS photocatalytic material using a low-temperature oil bath method. The difference from Example 1 is that steps S1-S3 are omitted, and only steps S4-S6 are retained. In step S4, VS4 material is not added, while the remaining steps and parameters remain unchanged. The product is denoted as low-temperature CuS.
[0054] Comparative Example 9: This comparative example provides a method for preparing CuS photocatalytic material using a high-temperature oil bath method. The difference from Comparative Example 1 is that steps S1-S3 are omitted, and only steps S4-S6 are retained. In step S4, VS4 material is not added, and the oil bath reaction temperature in step S5 is 140℃. All other steps and parameters remain unchanged. The product is denoted as high-temperature CuS.
[0055] "Low temperature" refers to photocatalytic materials prepared by a low temperature (80℃) oil bath method; "high temperature" refers to photocatalytic materials prepared by a high temperature (140℃) oil bath method; "TAA+VS" refers to VS materials treated with TAA by a low temperature oil bath method; "low temperature CuS+VS physical mixing" refers to the physical mixing of CuS materials and VS materials prepared by a low temperature oil bath method.
[0056] Comparative Example 10: This comparative example provides a method for preparing CuS@VS4 heterojunction photocatalyst material using a low-temperature oil bath method. The difference from Example 1 is that in step S2, the ball milling speed is 500 rpm, while the rest is the same as in Example 1. The product is designated as Low-Temperature CuS@VS-500.
[0057] Comparative Example 11: The difference between this comparative example and Example 1 is that in step S2, the rotation speed during the ball milling reaction is 100 rpm. Step S3 is modified to rinse the mixture alternately with water and ethanol after ball milling, and then dry it in a drying oven at 80°C. oDry at C for 10 hours to obtain a solid powder; Simultaneously delete steps S4-S6.
[0058] The product is denoted as V.
[0059] Comparative Example 12: In step S5 of this comparative example, the oil bath reaction temperature is 120°C, and the rest are the same as in Example 1.
[0060] The product is denoted as 120CuS@VS.
[0061] Table 1 shows the inductively coupled plasma mass spectrometry (ICP-MS) test results of the samples prepared in the embodiments and comparative examples 1 to 12 of this patent.
[0062] Table 1. ICP-MS measurements (atomic ratio, %) of samples prepared in Examples 1-12 and Comparative Examples.
[0063] As shown in Table 1, the molar ratio of V atoms to S atoms in the VS sample of Comparative Example 7 is 21.6:78.4 (corresponding to the molecular formula VS). 3.63 In the CuS samples grown at low temperature (Comparative Example 8) and high temperature (Comparative Example 9), the molar ratio of Cu atoms to S atoms was 50.32:49.68 (corresponding to the molecular formula CuS). 0.99 ) and 50.44:49.56 (corresponding to the molecular formula CuS) 0.98 This indicates that the VS sample has many sulfur defects, while the CuS samples prepared at both temperatures have almost no sulfur defects. After low-temperature growth of CuS on the VS surface, the molar ratio of Cu atoms:V atoms:S atoms in the low-temperature CuS@VS sample in Example 1 is 25.63:9.86:64.51. Assuming that the molecular formula of CuS remains unchanged during this process, the molecular formula of the low-temperature CuS@VS sample can be deduced to be CuS. 0.99 @VS 3.97 (Corresponding to Example 1) Compared with the VS sample, the sulfur defects inside were significantly repaired, which also proves that the epitaxial growth of CuS at low temperature can repair the numerous sulfur defects in VS4 obtained by ball milling, and solve the problem of aggravated sulfur defects. Furthermore, by changing the ball milling speed for preparing the VS material, when the speed was 500 rpm, the molecular formula of the product after CuS growth on its surface was CuS. 0.99 @VS 3.74(Comparative Example 10) This shows that excessively high ball milling speeds lead to an excess of sulfur defects in VS, exceeding the targeted repair capacity of CuS, thus significantly reducing the repair rate. When the speed is 100 rpm, insufficient speed prevents the provision of the energy required for the reaction, ultimately preventing the formation of VS material (Comparative Example 11). Therefore, a reasonable speed is a necessary condition for forming VS with an appropriate amount of sulfur defects. Similarly, if the temperature is too high during CuS growth, the CuS nucleation energy barrier decreases significantly with increasing temperature, leading to an excess of sulfur defects. 2- Before defect repair was completed, a large amount of sulfur was consumed in the non-directional growth of CuS, resulting in a significant decrease in the sulfur defect repair rate (sulfur defect content was 2.75%, corresponding to Comparative Example 12, which is 3.67 times that of CuS grown at 80℃ in Example 1). Furthermore, the sulfur defects in the low-temperature CuS+VS physical mixture sample (Comparative Example 6) were not repaired, indicating that the absence of chemical bonds or tight physical contacts is insufficient to trigger significant, large-scale charge transfer. Similarly, the molecular formulas of the high-temperature CuS@VS (Comparative Example 1), ZnS@VS (Comparative Example 2), PbS@VS (Comparative Example 3), and MIS@VS (Comparative Example 4) samples can be deduced to be CuS, ZnS, and MIS, respectively. 0.98 @VS 3.88 ZnS 0.99 @VS 3.76 PbS 0.99 @VS 3.71 and MnIn 1.97 S 3.95 @VS 3.83 It can be observed that although the sulfur defect density in these samples is smaller than that in the VS sample, a certain number of sulfur vacancies still exist (compared to the low-temperature CuS@VS sample). This indicates that when CuS, ZnS, or PbS is grown on the VS surface at high temperature, the sulfur content in the solution... 2- It tends to nucleate with metal ions in solution rather than bind with V atoms to fill sulfur defects. On the other hand, the VS sample treated with TAA (Comparative Example 5) has the molecular formula VS. 3.95 This indicates that S 2- It can effectively repair lattice defects in VS samples, providing a basis for using CuS to repair lattice defects in VS samples.
[0064] Table 2 shows the specific surface area and pore volume of the samples in Example 1 and Comparative Examples 1-9 of this patent.
[0065] Table 2. Specific surface area and pore volume of samples prepared in Example 1 and Comparative Examples 1-9
[0066] Characterization by specific surface area testing (BET) showed that the low-temperature CuS@VS sample had a surface area of 115.6 m². 2The highest specific surface area and largest pore volume per g indicate that the composite sample, after growing CuS nanosheets on the VS surface, has a larger specific surface area to provide the active sites required for photocatalytic reactions. This is mainly due to the controllable morphology of VS obtained by ball milling, and the significant increase in specific surface area of the composite material with a flower-like morphology obtained by growing CuS nanosheets on the nanoflower-like VS4 material. Notably, the specific surface area and pore volume of the low-temperature CuS+VS physical mixture sample are between those of the low-temperature CuS sample and the VS sample, indicating that physical mixing does not increase the specific surface area of the sample. In addition, the specific surface area of the VS sample treated with TAA did not increase significantly compared with VS, because the atomic-level sulfur defects have a limited impact on the morphology. On the other hand, the specific surface areas of the high-temperature CuS@VS, ZnS@VS, PbS@VS, and MIS@VS samples are smaller than those of the low-temperature CuS@VS sample, but larger than those of the VS sample, which is determined by their respective morphologies.
[0067] Figure 1 These are the spin electron resonance (ESR) spectra of the samples prepared in Example 1 and Comparative Examples 1-9 of this invention. Figure 1 It can be seen that the prepared VS, low-temperature CuS+VS physical mixture, PbS@VS, ZnS@VS, MIS@VS, and high-temperature CuS@VS samples all exhibit attenuation at g=2.004, corresponding to the ESR characteristic peak of sulfur defects. This indicates that these materials all contain sulfur defects, and the VS sample has the strongest ESR peak, indicating that it has the highest internal sulfur defect density.
[0068] On the other hand, the ESR peaks of high-temperature CuS, low-temperature CuS, TAA+VS, and low-temperature CuS@VS samples were not obvious, which indicates that: (1) CuS lattice is stable and temperature has almost no effect on the formation of sulfur defects inside it; (2) the sulfur defect density inside the VS sample after TAA treatment and low-temperature CuS growth is significantly reduced, that is, the sulfur in the solution during TAA and low-temperature CuS growth is reduced. 2- It can promote the repair of sulfur defects inside VS because Cu 2+ and S 2- The binding energy is less than V 4+ and S 2- The binding energy of S, therefore S 2- More inclined to V 4+ This binds to fill the sulfur defect sites, while the sulfur released when TAA dissolves in water... 2-The CuS directly participates in the repair of sulfur defects, resulting in weak ESR peaks in both samples. Changing the temperature conditions, the ESR characteristic peak of the high-temperature CuS@VS sample was stronger than that of the low-temperature CuS@VS sample, but weaker than that of the untreated VS sample. This indicates that under high-temperature conditions, the fast reaction rate causes CuS to tend to nucleate and grow on its own, rather than diffuse to the sulfur defects in VS and combine with V. This proves that low temperature is a necessary condition for the repair reaction.
[0069] Furthermore, the ESR peak intensity of the low-temperature CuS+VS physical mixture sample is approximately 90% of that of the VS sample, indicating that physical contact cannot repair sulfur vacancies, highlighting the necessity of the epitaxial growth reaction interface. In contrast, the ESR peaks of the PbS@VS, ZnS@VS, MIS@VS, and high-temperature CuS@VS samples decrease sequentially, to approximately 60%, 50%, 45%, and 40% of those of the VS sample, respectively. This is partly because the introduction of PbS and other substances during VS recombination reduces the density of sulfur defects in the composite sample due to a "dilution" effect, and the paramagnetic quenching of sulfur defects caused by interfacial charge transfer further reduces the number of effective paramagnetic centers, resulting in a weaker ESR than the original VS sample. On the other hand, the relatively strong ESR peaks still present in these samples are due to their tendency towards self-nucleation growth during recombination, rather than S nucleation. 2- With V 4+ Combined with the repair of sulfur defects.
[0070] Figure 2 The images show the X-ray diffraction (XRD) patterns of the samples prepared in Examples 1, 1-5, and 7-9 of this invention, wherein (a) is the XRD pattern of the samples prepared in Comparative Examples 5 and 7-9; and (b) is the XRD pattern of the samples prepared in Examples 1 and 1-4. Figure 2 (a) It can be seen that the characteristic peaks of the prepared VS (Comparative Example 7), low-temperature CuS (Comparative Example 8), and high-temperature CuS (Comparative Example 9) samples are consistent with their respective standard XRD cards, indicating that they were all successfully prepared. After TAA treatment of the VS sample (Comparative Example 5), the full width at half maximum (FWHM) of the characteristic peak at 15.8° decreased from 0.45° to 0.22°, indicating that the TAA+VS sample has better crystallinity after repairing the sulfur defects in the VS material. On the other hand, the FWHM of the characteristic peak of CuS at 47.9° remained unchanged at 0.6°, indicating that temperature has little effect on the structure of CuS during its formation.
[0071] Figure 2(b) The low-temperature CuS@VS, high-temperature CuS@VS, ZnS@VS, PbS@VS, and MIS@VS samples shown all agree with their respective standard XRD cards, indicating that they were all successfully prepared. Notably, low-temperature CuS growth on the VS surface reduced the full width at half maximum (FWHM) of the characteristic peak at 15.8° in the low-temperature CuS@VS sample from 0.45° to 0.21°, while the high-temperature CuS@VS sample showed a 0.03° reduction compared to the VS sample. This indicates that under low-temperature conditions, CuS effectively repairs the lattice defects of VS, thereby greatly improving its crystallinity. At high temperatures, CuS tends to nucleate and grow on its own, thus having a limited effect on lattice repair in VS. Similarly, during the formation of ZnS@VS and PbS@VS, S... 2- Priority with Zn 2+ and Pb 2+ It combines with, rather than participates in, filling sulfur defects in VS. As for the full width at half maximum (FWHM) of the characteristic peak of VS at 15.8° in the MIS@VS sample, it is also significantly reduced compared to VS. This is because epitaxial growth under lattice matching repairs the lattice distortion in VS, which also significantly enhances its crystallinity.
[0072] Figure 3 These are scanning electron microscope (SEM) images of the samples prepared in Examples 1, 1-4, and 7 of this invention, where (a), (b), (c), (d), (e), and (f) are SEM images of the samples prepared in Comparative Example 7, Example 1, and Comparative Examples 1-4, respectively. Figure 3 (a) It can be seen that the VS sample exhibits a flower-like structure composed of nanosheets, which gives it a large specific surface area. Figure 3 (bc) shows the nanoflower morphology of the low-temperature CuS@VS and high-temperature CuS@VS samples. The similar morphology indicates that the reaction temperature has little effect on the morphology. Figure 3 (df) shows the small and thick nanosheets of ZnS@VS, the nanoparticles of PbS@VS, and the micron flower morphology of MIS@VS, which well explain the relationship between the specific surface areas of these samples.
[0073] Figure 4 The figures show the photocatalytic performance of the samples prepared in Example 1 and Comparative Examples 1-12 of this invention, where (a) and (b) are the degradation rate and degradation rate constant curves of tetracycline hydrochloride prepared in Example 1 and Comparative Examples 1-12, respectively. Figure 4(a) It can be seen that the TAA-treated VS sample exhibits better degradation performance than the untreated VS sample. Furthermore, after low-temperature CuS growth, the photocatalytic degradation efficiency of tetracycline hydrochloride by the low-temperature CuS@VS sample reached 97.9% after 2 hours. The photocatalytic degradation performance of the low-temperature CuS+VS physical mixture sample, however, falls between that of the VS and low-temperature CuS samples, showing no significant improvement. This indicates that the repair of VS lattice defects and the synergistic effect of the heterojunction can significantly enhance the photocatalytic performance of the low-temperature CuS@VS sample. In comparison, the photocatalytic degradation performance of the 120CuS@VS, low-temperature CuS@VS-500, ZnS@VS, PbS@VS, and MIS@VS samples are shown in Table 1 and... Figure 1 The observed sulfur defect density pattern is consistent: the lower the sulfur defect density, the better the photocatalytic performance of the composite sample. Figure 4 (b) The observed patterns and ESR results also correspond one-to-one. After lattice defect repair and heterostructure construction, the low-temperature CuS@VS sample exhibits 1.89 h -1 The degradation rate of tetracycline hydrochloride was 47.3 times, 17.2 times, and 23.6 times that of the untreated VS sample, the low-temperature CuS sample, and the low-temperature CuS+VS physical mixture sample, respectively. Although the photocatalytic performance of the ZnS@VS, PbS@VS, and MIS@VS samples, which failed to repair lattice defects, was improved compared to the VS material under the action of the heterojunction, it was still lower than that of the low-temperature CuS@VS sample.
[0074] Figure 5 The figures show the photocatalytic performance of the samples prepared in Example 1 of this invention. (a) is a rate curve of the photocatalytic degradation of several common organic pollutants and heavy metals by the samples prepared in Example 1; (b) is a bar chart comparing the stability of the samples prepared in Example 1 against tetracycline hydrochloride degradation over 5 cycles, with each cycle consisting of a continuous 2-hour degradation experiment. (The information can be found in the original text.) Figure 5 As shown in (a), the low-temperature CuS@VS sample has a significant degradation effect on tetracycline hydrochloride, rhodamine B, hexavalent chromium ions and phenol, covering antibiotics, organic dyes, heavy metals and chemical wastes. In particular, the degradation efficiency of rhodamine B and hexavalent chromium ions reached almost 100% in 60 minutes, showing its good multifunctional photocatalytic performance. Figure 5 (b) shows that the low-temperature CuS@VS sample maintained a degradation efficiency of over 90% after 5 cycles of degradation reaction accumulating 10 hours, demonstrating its excellent photocatalytic stability. These results indicate that the low-temperature CuS@VS sample prepared in this patent embodiment has good commercialization prospects.
[0075] Figure 6The figures show the current density curves of the samples prepared in Example 1 and Comparative Examples 1-9 of this invention, wherein (a) is the current density curve of the samples prepared in Comparative Examples 5-9; and (b) is the current density curve of the samples prepared in Example 1 and Comparative Examples 1-4. Figure 6 (a) It can be seen that the photocurrent density of the VS sample after TAA treatment is higher than that of the untreated VS sample. The low-temperature CuS+VS physical mixture sample is between the low-temperature CuS and VS samples, indicating that the physically mixed samples are independent systems and cannot achieve the purpose of repairing lattice defects. The pattern it exhibits is consistent with the previous experimental results. From Figure 6 (b) It can be seen that the low-temperature CuS@VS sample after low-temperature CuS growth exhibits the highest photocurrent density, which is approximately 5.9 times, 4.3 times, 3.0 times, and 1.8 times that of the PbS@VS, ZnS@VS, MIS@VS, and high-temperature CuS@VS samples, respectively. This indicates that it has the fastest carrier migration rate and indirectly proves the effectiveness of low-temperature CuS growth in repairing VS lattice defects.
[0076] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a heterojunction photocatalyst, characterized in that, A heterojunction is formed by combining CuS and VS4. The process of forming the heterojunction is as follows: CuS nanosheets are epitaxially grown on VS4 material to obtain CuS@VS4 heterojunction photocatalytic material.
2. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that, The epitaxial growth process is performed under low-temperature oil bath conditions; During the low-temperature oil bath, the oil bath temperature is 80~100℃. o C, the reaction time is 1~3h.
3. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that, Includes the following steps: Vanadium powder, thiourea and thioacetamide were mixed to obtain a slurry. The slurry was then ball-milled and post-processed to obtain VS4 powder. The obtained VS4 powder was added to glycerol, and then copper chloride and thioacetamide were added and ultrasonically dispersed. The mixture was then reacted in an oil bath and post-treated to obtain CuS@VS4 heterojunction photocatalytic material.
4. The method for preparing a heterojunction photocatalyst according to claim 3, characterized in that, When preparing VS4 powder, the molar ratio of sulfur source to vanadium powder is 1:(0.15~0.25), and the sulfur source is thiourea and thioacetamide; Vanadium powder, thiourea, and thioacetamide were added to ethanol and mixed. After ultrasonic dispersion, a mixed slurry was obtained. The volume ratio of the solid substances in the mixed slurry to the volume of ethanol was (1 mol): (0.25~2 L). The solid substances were thiourea, thioacetamide, and vanadium powder.
5. The method for preparing a heterojunction photocatalyst according to claim 3, characterized in that, When preparing VS4 powder, the ball milling speed is 200~300 rpm and the time is 5~18 h.
6. The method for preparing a heterojunction photocatalyst according to claim 3, characterized in that, During ball milling, the volume ratio of grinding balls to precursor raw materials is 1:(0.025~0.25), and the volume ratio of the total solid volume formed by the grinding balls and precursor raw materials to the volume of ethanol used in the ball milling reaction is 1:(1~5). And / or, during ball milling, the mode is set to rotate clockwise for 5-10 minutes, then pause for 1-2 minutes, then rotate counterclockwise for 5-10 minutes, and so on until the predetermined ball milling time is reached.
7. The method for preparing a heterojunction photocatalyst according to claim 3, characterized in that, The molar ratio of VS4 material to copper chloride is 1:(1~5), and the molar ratio of copper chloride to thioacetamide is 1:(1~1.5).
8. A method for preparing a heterojunction photocatalyst according to any one of claims 2 to 7, characterized in that, The post-processing for preparing VS4 powder involves sequential filtration, washing, and drying. The post-treatment process after the oil bath reaction consists of centrifugation, washing, and drying in sequence. The centrifugation is performed in a centrifuge with a speed of 4000~8000 rpm for 2~10 minutes; The washing process involves washing the sample five or more times with deionized water and anhydrous ethanol alternately. The drying temperature is 70~90°C. o C, drying time is 6~24h.
9. A heterojunction photocatalyst, characterized in that, It is obtained by the preparation method described in any one of claims 2 to 8.
10. The application of the heterojunction photocatalyst according to claim 9 in the photocatalytic degradation of organic pollutants; The organic pollutant is at least one of tetracycline hydrochloride, phenol, rhodamine B, and phenol.
Citation Information
Patent Citations
A vanadium tetrasulfide / vanadium carbide composite material and its preparation method and application
CN114744152B
Preparation of high-specific-capacity porous heterojunction tin-based sulfide of sodium battery
CN118448609A
Cited By
CuS with sulfur-rich defect as well as preparation method and application of CuS
CN121342077A